CLINICAL AND DIAGNOSTIC VALUE OF PROCALCITONIN LEVELS IN VICTIMS OF SEVERE CONCOMITANT INJURY - Yu. S. Polushin; A. A. Afanasyev; L. P. Pivovarova; M. E. Malyshev (Вестник анестезиологии и реаниматологии, 2017)
Mortality due to pyoseptic complications after severe mechanical injury is rather high. Some hopes for its reduction are associated with the timely detection of infectious complications. In this case an important role is, in terms of early diagnosis, attached to the calcitonin prohormone procalcitonin that is positioned itself as a marker for the progression of a bacterial infectious process. At the same time, there is evidence for elevated PCT levels after extensive surgical interventions and in massive injuries directly unassociated with the development of an infectious process. Objective: to estimate the significance of its changes early after injury. A prospective investigation was conducted, which enrolled 76 victims of severe concomitant mechanical injury (patients with severe brain injury and victims whose death had occurred within the following few days were excluded from the study). The time course of changes in the blood levels of PCT, C-reactive protein, activated monocytes expressing receptors for lipopolysaccharide and other bacterial antigens (CD14+ and HLA-R+), cytokines (IL-6, IL-10), glucose, and lactate was studied on admission, at 12 and 24 hours, 3, 7, and 10 days. The diagnosis of bacteremia involved blood microbiology tests for sterility and polymerase chain reaction to detect antigens of blood opportunistic microorganisms. The findings were analyzed in view of injury severity scores (ISS), the development of infectious complications, and an outcome. PCT concentrations were shown to rise significantly within the first 24 hours after injury in the absence of clinical manifestations of infectious complications. The increase in PCT levels was preceded by the highest rise of HLA-DR+ within the first 24 hours and CD14+ just 12 hours after injury, which could not preclude the bacterial translocation inducing, along with other factors, the development of a systemic inflammatory response. At the same time, the findings could suggest that the role of this indicator must not boil down exclusively to the function of that of infectious complications.